Implementation of Lumbosacral Vertebrae Examination in the Erect Patient Position Based on Clinical Diagnosis of Low Back Pain (LBP) - Priyanto, Rachmat; Laksono, Muharram Budi; Setiawan, Rudi; Sumarmi; Haryani, Ani (Universitas An Nasher - Cirebon, 2025)
Background: Low back pain (LBP) is one of the most common musculoskeletal complaints encountered in healthcare settings, thus requiring accurate diagnostic management to support clinical diagnosis. Radiographic examination of the lumbosacral vertebrae in the erect position is one of the essential procedures in evaluating this condition. Purpose: This study aims to determine the implementation of lumbosacral vertebrae radiographic examinations in patients with LBP at the Radiology Department of Majalengka Regional General Hospital (RSUD Majalengka), starting from data verification to the interpretation of results by a radiology specialist. Method: This study employed a descriptive method with an observational approach to the radiographic procedure using anteroposterior (AP) and lateral projections. Results: The findings indicate that the implementation of the examination was carried out properly, as evidenced by the appropriate patient positioning, adequate radiation protection, and radiographic images that met diagnostic quality criteria. Interpretation by the radiology specialist confirmed that the images produced were suitable for establishing a diagnosis of low back pain.